The Use of Euphemisims in the Report Card Comment in Canggu Community School - Gusti Ayu Ketut Astiti (Lingua Scientia, 2011)
The use of euphemism in the process of human interaction is very common a linguistic phenomenon. The correct use of euphemisms is to avoid the embarrassment of interpersonal communication or unpleasant, so as to achieve a successful interaction purposes. In today’s society, euphemisms have been widely used in various fields. This study concerns on the use of euphemisms in writing report card comments by teachers of Canggu Community School. The use of euphemisms in reporting students’ achievement relates to the teachers’ politeness strategies to save the students’ and parents’ face or to minimize the students FTAs. Based on the data from the report card comments and interview with the teachers about the students, it is found that teachers in Canggu Community School mostly employ euphemisms in their comments on three areas of achievement: academic, work presentation and behavior. They also employ Grice’s cooperative principles. Only few comments do not employ euphemism but rather informing as informative as possible in a polite way.